2017
DOI: 10.1371/journal.pone.0179710
|View full text |Cite|
|
Sign up to set email alerts
|

Human alpha defensin 5 is a candidate biomarker to delineate inflammatory bowel disease

Abstract: Inability to distinguish Crohn's colitis from ulcerative colitis leads to the diagnosis of indeterminate colitis. This greatly effects medical and surgical care of the patient because treatments for the two diseases vary. Approximately 30 percent of inflammatory bowel disease patients cannot be accurately diagnosed, increasing their risk of inappropriate treatment. We sought to determine whether transcriptomic patterns could be used to develop diagnostic biomarker(s) to delineate inflammatory bowel disease mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 50 publications
2
42
0
Order By: Relevance
“…A previous study demonstrated a deficiency of human α-defensin expression in subjects with IBD [29]; and defensins released by Paneth cells appear to be critical in the pathogenesis and progression of IBD [30,31]. Besides, human α-Defensin-5 could be used as a potential candidate biomarker to molecularly differentiate Crohn's colitis (high levels of Human α-Defensin-5) from UC (low levels of Human α-Defensin-5) [32]. In this study, we used the typical DSS mouse model of colitis to test the effects of α-defensin administration in the pathophysiology of colitis.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study demonstrated a deficiency of human α-defensin expression in subjects with IBD [29]; and defensins released by Paneth cells appear to be critical in the pathogenesis and progression of IBD [30,31]. Besides, human α-Defensin-5 could be used as a potential candidate biomarker to molecularly differentiate Crohn's colitis (high levels of Human α-Defensin-5) from UC (low levels of Human α-Defensin-5) [32]. In this study, we used the typical DSS mouse model of colitis to test the effects of α-defensin administration in the pathophysiology of colitis.…”
Section: Discussionmentioning
confidence: 99%
“…DEFA5 encodes a family of antimicrobial and cytotoxic peptides thought to be involved in host defense [29]. It is reported as a candidate biomarker for Crohn's disease [48]. PRG4 encodes a large proteoglycan [29].…”
Section: Rab21 and Ninj1 Are Related To Cell Adhesion And Migration mentioning
confidence: 99%
“…Therefore, a total of 30% of colonic IBD patients are not diagnosed accurately [258][259][260]. For these reasons, efforts at identifying accurate, noninvasive biomarkers have been undertaken [263][264][265]. Another really challenge is a significant subgroup of IBD patients, especially UC patients undergoing proctocolectomy that convert to de novo Crohn's, are thought to be "misdiagnosed" [265].…”
Section: Clinical Diagnosismentioning
confidence: 99%
“…For these reasons, efforts at identifying accurate, noninvasive biomarkers have been undertaken [263][264][265]. Another really challenge is a significant subgroup of IBD patients, especially UC patients undergoing proctocolectomy that convert to de novo Crohn's, are thought to be "misdiagnosed" [265]. This may not be accurate because there is a possibility that these patients with UC were "transformed" due to an altered microbiome ecology in the pouch and immune environment and that the patient actually "convert".…”
Section: Clinical Diagnosismentioning
confidence: 99%
See 1 more Smart Citation